Peran Bimbingan Dan Konseling Melalui Metode Pembiasaan Dalam Membentuk Karakter Pada Anak Usia Dini (Al-INSAN Jurnal Bimbingan Konseling dan Dakwah Islam, 2022)
Children have a very vulnerable period of growth and development. For this reason, during the growth and development period in children, it is very appropriate to shape the character of early childhood to be more positive. The formation of early childhood character can be done through the habituation method. The habituation method is a method that is repeated until the desired character appears. In guidance and counseling, this habituation method is a behavioral counseling theory with operant conditioning. This research is qualitative research. The method used in this research is design research or research design that aims to collect and process data so that it can be carried out to achieve research objectives. While analyzing the data obtained using all the data, reducing the data, presenting the data, and verifying the data. The results of this study indicate that activities carried out repeatedly will shape the character of the child himself. The activities carried out are daily activities carried out at the school in accordance with the Daily Learning Plan (RPPH) which is prepared either programmed or not. Methods of habituation can be done through 1). These programmed activities can be carried out with special planning within a certain period of time to develop children's character individually, in groups, and classically. 2) non-programmed activities can be carried out with: routine activities (flag ceremony, praying before and after doing activities, shaking hands), spontaneous activities (disposing of garbage in its place, giving and returning greetings), and exemplary (dressing neatly, speaking politely, saying thanks and sorry).